Rancang Bangun 2D Game Pemilahan dan Dampak Sampah Menggunakan Game Engine Unity Berbasis Desktop - Latifah, Ayu; Mohamad Bahari, Aslah (Institut Teknologi Garut, 2025)
Waste is solid material left over from living organisms' activities that is no longer used. Waste poses a serious threat to the environment and health because it is difficult to decompose. Uncontrolled accumulation can cause pollution, spread disease, and trigger disasters such as floods that threaten the welfare of the community and environmental sustainability. This study aims to raise awareness about waste management through the development of an educational game as an interactive learning medium. The game is designed to convey messages about the importance of waste sorting and its impact on the ecosystem in an interesting and easy-to-understand manner. The development was carried out using a methodology that integrates attractive visual elements with learning materials structured based on structured instructional objectives. The result of this research is a game application for education on waste issues, conveying moral values and concern for the environment in community life.